The effect of visual motion stimulus characteristics on vection and visually induced motion sickness - Keshavarz, Behrang; Phillip-Muller, Aaron E.; Hemmerich, Wanja; Riecke, Bernhard E.; Campos, Jennifer J. (Displays, 2018)
Several factors contribute to the likelihood of experiencing illusory sensations of self-motion (i.e., vection) in Virtual Reality (VR) applications. VR users can also experience adverse effects such as disorientation, oculomotor issues, or nausea known as visually induced motion sickness (VIMS). The goal of the present study was to systematically investigate three characteristics of visual motion stimuli —speed, density, and axis of rotation—and how they relate to both vection and VIMS. Two experiments were conducted. In Experiment 1, a stereoscopic stimulus containing a star field of white spheres on a black background was presented to 21 participants. The stimulus contained linear forward motion (expanding optic flow) and was varied with respect to a) density (lower, higher) and b) speed (faster, slower). Ratings of vection (onset time, intensity, duration), VIMS (measured via FMS, SSQ), and presence were recorded. In Experiment 1 vection was found to be strongest under faster and higher density conditions. VIMS was overall minimal and not affected by either speed or density. In Experiment 2, rotation along the pitch, yaw, or roll axes were added to the stimulus that created the strongest vection in Experiment 1, resulting in spiral/curvilinear motion profiles. Again, subjective ratings of vection, VIMS, and presence were collected. Results showed that vection intensity was significantly increased when pitch or roll rotation were added to forward motion. Despite overall low VIMS scores, pitch rotation resulted in the highest FMS scores and significantly more disorientation as measured by the SSQ. No correlations between the vection and VIMS measures were observed. Overall, these results suggest that all three stimulus’ characteristics can alter the sensation of vection and can have additive effects, but that this increase in vection is not necessarily associated with increases in VIMS.
Keywords: Riecke; Riecke_2018; aaron-philip-muller; behrang-keshavarz; bernhard-riecke; jennifer-campos; journalPaper; vection; wanja-hemmerich